Chinese investment in Africa - Guo, Zhida (2020)
The history of Chinese investment in Africa did not last long, but it brings a lot of discussions. Some people think that investment is opaque; some people think that the amount of investment is confusing; some people think that Chinese investment in Africa has provided a lot of help for Africa, and some people believe that this is new. The embodiment of colonialism, this paper describes the sectors and areas in which Chinese investments are going through, and at the same time, depicts loans and debt issues and finally gives some opinions and suggestions.